Morfologi dan Nilai Taksonomi Serbuk Sari Impatiens (Balsaminaceae) - Sukarsa Sukarsa; Agus Pudjoarinto; Nanda Utami (Floribunda, 2002)
Morphology and taxonomical values of pollen grains of Impatiens (Balsaminaceae)